Breaking the cycle of abusive supervision: How disidentification and moral identity help the trickle-down change course - TAYLOR, Shannon G. (Institutional Knowledge at Singapore Management University, 2019)
Studies show that abusive leader behaviors "trickle down" to lower organizational levels, but this research ignores that many abused supervisors do not perpetuate abuse by harming their own subordinates. Drawing on social-cognitive theory and related research, we suggest abused supervisors might defy rather than emulate their managers' abusive behavior. Specifically, we predicted that some abused supervisors-namely, those with strong moral identities-might in effect "change course" by engaging in less abuse or demonstrating ethical leadership with their subordinates to the extent they disidentify with their abusive managers. Across 2 experiments (n = 288 and 462 working adults, respectively) and a field study (n = 500 employees and their supervisors), we show that relations between manager abuse and supervisors' abusive and ethical behaviors were carried by supervisors' disidentification, and that the direct and indirect effects of manager abuse were stronger for supervisors with comparatively higher moral identity levels. We discuss our findings' implications and avenues for future research.